1999
DOI: 10.1071/ph98107
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Viscosity and Particle Creation in Brans - Dicke Theory

Abstract: The effect of bulk viscosity on the evolution of the spatially flat Friedmann–Lemaitre–Robertson–Walker (FLRW) models in the context of open thermodynamical systems, which allow for particle creation, is analysed within the framework of Brans–Dicke (BD) theory. The BD field equations are modified with the incorporation of a creation pressure and bulk viscous stress. A class of physically plausible models has been taken into consideration. The behaviour of the particle number density and bulk viscosity is discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 2 publications
(4 reference statements)
1
22
0
1
Order By: Relevance
“…They found that the adiabatic creation of massive particles implies power-law inflation. Sudharsan and Johri (1994), Johri and Desikan (1996), Desikan (1997), Singh and Beesham (1999), and Singh et al (2002) have studied cosmological models with particle creation using Prigogine et al's hypothesis in general relativity and some of its modified theories. After the discovery of the accelerating universe, this model was reconsidered to explain it and got some unexpected results.…”
mentioning
confidence: 98%
“…They found that the adiabatic creation of massive particles implies power-law inflation. Sudharsan and Johri (1994), Johri and Desikan (1996), Desikan (1997), Singh and Beesham (1999), and Singh et al (2002) have studied cosmological models with particle creation using Prigogine et al's hypothesis in general relativity and some of its modified theories. After the discovery of the accelerating universe, this model was reconsidered to explain it and got some unexpected results.…”
mentioning
confidence: 98%
“…Following Luis (1985), Johari and Kalyani (1994), Singh and Beesham (1999) and recently Singh and Kale (2009), we assume the well accepted power law relation between gravitational constant G and scale factor a as…”
Section: Solutions Of the Field Equationsmentioning
confidence: 99%
“…Shri Ram and Singh (1997) studied the effect of timedependent bulk viscosity on the radiation of Friedmann models with zero curvature in BD theory. Singh and Beesham (1999) studied the effect of bulk viscosity on the evolution of the spatially flat Friedmann-Lemaitre-RobertsonWalker models in the context of open thermodynamical systems, which allow for particle creation, analyzed within the framework of BD theory. Reddy et al (2007) discussed the homogeneous axially symmetric Bianchi type-I radiating cosmological model with negative constant deceleration parameter in BD scalar-tensor theory gravitation.…”
Section: Introductionmentioning
confidence: 99%